(untitled) (Economics and region, 2023)
The study systematises and summarises theoretical and practical methods and approaches to improving the efficiency of construction companies within the framework of the concept and strategies of sustainable development. Sustainable methods in construction provide an increase in revenues and economic value of companies, creating value for customers. Sustainable construction project management methods provide increased value to clients while maintaining acceptable costs. The construction business combines strategies and methods to save resources, materials, water and land. The financial dimension of efficiency involves the use of an economic valuation approach based on life-cycle costing, which allows forecasting construction costs from the operation phase through maintenance and replacement to the end of the service life. Based on the analysis of the cases of the world’s leading construction companies, the author determines that the concept of sustainable development of the construction industry involves the implementation of a targeted and comprehensive approach to business activities. The practical significance of the research results lies in proving the efficiency of construction based on the experience of world leaders in the industry. Prospects for further research in this area are empirical studies of the economic efficiency of construction enterprises at the international and national levels.